Characteristics of lactic acid bacteria, microbial community and fermentation dynamics of native grass silage prepared in Inner Mongolian Plateau - Hou, Meiling; Wang, Zhijun; Sun, Lin; Jia, Yushan; Wang, Shicong; Cai, Yimin (Frontiers in Microbiology, 2023)
To prepare high quality silage, we studied the chemical composition, silage fermentation, characterization, and identification of lactic acid bacteria (LAB) associated with silage fermentation of native grass on Inner Mongolian plateau. LAB were isolated from fresh native grass, and their silage was prepared using a small-scale fermentation system. The dominant species of native grasses used were Stipa baicalensis, Leymus chinensis, Cleistogenes squarrosa, Melissilus ruthenicus and Pulsatilla turczaninovii, which contained 47.83-59.43 %FM moisture and 8.72-14.55 %DM crude protein. When silage was prepared with these native grasses, good preservation with a relatively low pH (below 4.44) and high (p<0.05) lactic acid content (>0.58 % of FM) were obtained. Based on the morphological and biochemical characteristics, these isolates were divided into 12 groups (A-L). All isolate strains were gram-positive and catalase-negative bacteria that produce lactic acid from glucose. Group A - K were cocci, while group L was rod-shaped. Group A-E formed D-lactic acid, but group H-K formed L-lactic acid, and other groups formed DL-lactic acid. Group A-E were heterofermentative, and Group F-L were homofermentative types of LAB. According to the 16S rRNA gene sequences analysis, strains were identified as genus Leuconostoc (A, B, and C), Weissellla (D, E), Pediococcus (F, G), Enterococcus (H, I, J and K), and Lactiplantibacillus (L). Enterococcus (E.) faecium (29.17 %, percentage of total isolates) and Pediococcus (P.) acidilactici (18.75 %) were the most frequently occurring dominant species. Other LAB populations included E. faecalis (14.58 %), Leuconostoc (Le.) pseudomesenteroides (8.33 %), Weissella (W.) kimchii (6.25 %), P. pentosaceus (6.25 %), Lactiplantibacillus (L.) plantarum (4.17 %), W. cibaria (4.17 %), Le. mesenteroides subsp. dextra (2.08 %), Le. citreum (2.08 %), E. durans (2.08 %) and E. saccharolyticu (2.08 %). This study suggests that the native grasses contained abundant LAB species, and they can be used as good-quality silages in animal husbandry.